Seismicity and earthquake risk in Portugal - Bezzeghoud, M. (2006)
The workshop “Earthquake monitoring and Earthquake Risk in WEstern Mediterranean” (EERWEM) will summarize the current knowledge, on-going projects and research plans with regard to seismic activity and risk in the region. This work is organized in two topics: i) presentation of our current research on seismic activity and earthquake risk in the Western Mediterranean region, particularly in Portugal and ii) a short training course about seismic data processing and waveform analysis. Some applications based on broad band teleseismic wave form will be presented using software currently available on the internet sites. Ongoing research projects within the group will be presented and discussed. Some preliminary results will be shown, in particular for the following research topics: i) Seismic Tomography of the Continental Lithosphere of Algarve (Portugal); ii) Finite seismic source modelization and strong motion prediction in Portugal and iii) the University of EVOra (UEVO) Broad Band seismic station (STS2) and upcoming temporary broad band network.